The Knowledge of Lombok Praya-Indonesia Regional Community on the Safety Use of Medicinal Plants - Wiwied Ekasari; Suko Hardjono; Sugijanto Sugijanto; Juni Ekowati; I Nyoman Wijaya; Tri Widiandani (Berkala Kedokteran, 2021)
Abstract: The use of medicinal plants to maintain or overcome health problems has long been carried out by worldwide community. Along with the development of knowledge, data about the existence of undesirable effects or side effects associated with the use of medicinal plants that are not appropriate are obtained. This research is conducted to determine public knowledge about the safety several medicinal plants use. The study was conducted with a questionnaire technique in Lombok Praya, Indonesia. The results show that knowledge about the safety of the use of medicinal plants in breastfeeding mothers obtains the correct answer by 48%, knowledge about the parts of medicinal plants that are dangerous for consumption by 39% and knowledge about medicinal plants that can increase health risks by 21%. Whereas, the knowledges for the use of medicinal plants in pregnant women and the use of medicinal plants that are not right obtains very good results with correct answers of 79% and 81%. Based on further interviews, these good results are obtained because they are supported more by traditional use of the plant that has already existed in the area. Public understanding of the safety of some medicinal plants in Lombok Praya is still lacking. It is necessary to add knowledge about the use of medicinal plants that requires special attention, especially on plants that are often used by people in the area. Local health agencies need to disseminate information on the safety of medicinal plants that is wider and more sustainable. Keywords: Community, medicinal plant, safety, public understanding.